Does formal work pay? The role of labor taxation and social benefit design in the New EU Member States - Johannes Koettl; Michael Weber (Institute for the Study of Labor (IZA), 2012)
The analysis presented in this paper defines three different synthetic measurements of disincentives for formal work: two standard measurements, namely the tax wedge and the marginal effective tax rate (METR); and a new, innovative measurement called formalization tax rate (FTR). The novelty of the latter is that it measures disincentives stemming not only from labor taxation, but also from benefit withdrawal due to formalization. A descriptive analysis across a large number of OECD and Eastern European countries reveals that the disincentives for formal work - when measured through the FTR - are especially high for low-wage earners. This suggests that formal work might not pay in this segment of the labor market, in particular for the so-called mini-jobs and midi-jobs (low paying part-time work). Another novelty of the paper is its empirical approach. Using EU-SILC 2008 data and OECD Tax and Benefit data for six Eastern European countries (Bulgaria, Czech Republic, Estonia, Latvia, Poland, and Slovakia), we match disincentives for formal work to individual observations in a large data set. Applying a probit regression, the analysis finds a significant positive correlation between FTR or METR and the incidence of being informal. In other words, controlling for individual and job characteristics, the higher the FTR or the METR that individuals are facing is, the more likely they are to work informally. The tax wedge, on the other hand, yields a negative correlation. This indicates that the tax wedge is not sufficiently capturing disincentives for formal work. We also conclude that in cross-country analysis, it might be more useful to use the tax wedge that applies to low wage earners as opposed to average wage earners.
urn:nbn:de:101:1-201204239905
Keywords: H26; J32; O17; 330; tax evasion; non-wage labor costs and benefits; informal employment; measurement of work disincentives; formalization tax rate; Lohnsteuer; Steuerbelastung; Excess Burden; Ökonomischer Anreiz; Schwarzarbeit; Niedriglohn; OECD-Staaten; Osteuropa